Filosofia e Direitos Humanos: por uma articulação para consolidação da educação em direitos humanos na escola - Queiroz, Francisca Karla Ferreira de (2020)
In Brazil, the Federal Constitution of 1988 institutionalized human rights in the country, highlighting citizenship and the dignity of the human person as fundamental principles of the Brazilian State. In 2003, Education in Human Rights became public policy. Based on this context, and in line with the National Guidelines for Education in Human Rights, this work has the general aim of demonstrating the need for articulation between the teaching of Philosophy and Education in Human Rights through an experience of interventional practice that takes as a reference the theoretical elaborations of Theodor Adorno on the critical and emancipatory potential of education and Philosophy. From this perspective, in teaching of Philosophy at the secondary level, it is pointed out the need for the formulation of pedagogical proposals aimed at real training, and not at the mere instruction (semi-training) of the subjects, with a view to sensitize them about the scenario of intense violations of human dignity. They has chosen the action research method and reflected on the pedagogical didactic aspects, using primarily Rodrigo (2009) and Candau (2008). They worked as a methodological strategy through pedagogical workshops with students of the 2nd grade of high school at the Maria Ângela da Silveira Borges State School of Professional Education (Fortaleza-CE). In conclusion, this intervention action positively affected the student’s conscience and behavior, where it awakened them to the relevance of the discussion on human rights and contributed to their deepening by enabling the confrontation between the concepts gained at the level of common sense and the theoretical knowledge produced by Philosophy. Also, it has contributed to the development of the argumentative capacity of the students, necessary for the autonomous exercise of democracy beyond the classroom space.